Evaluasi Sifat Kimia Tanah pada Lahan Kopi di Kabupaten Mandailing Natal - Wilson Wilson; Supriadi Supriadi; Hardy Guchi (Jurnal Agroekoteknologi, 2015)
This research purposed to evaluate soil chemistry characteristic on coffee land in Mandailing NatalRegency and to know the relationship of soil chemistry characteristic to production which held oncoffee land in Mandailing Natal Regency, Research and Technology Laboratory Agriculture FacultyNorth Sumatra University and Soil Biology Laboratory Agriculture Faculty North Sumatra University.Data is obtained by survey system and data sample is gotten expressly (Purposive Random Sampling)with six parametres i.e. pH, Organic Carbon, Total Nitrogen, Available Phosphate, Cation ExchangeCapacity, and Base Saturation. Data is tested by using assumption classic test i.e. outlier test,normality, linearity, correlation analyze and quadratic regression. The research result show that soilchemistry characteristic is not obviously relationship to production.Keyword : soil chemistry characteristic, coffee production, regression